Vitamin D-binding protein, total, “nonbioavailable,” bioavailable, and free 25-hydroxyvitamin D, and mortality in a large population-based cohort of older adults - Zhu, Anna; Kuznia, Sabine; Niedermaier, Tobias; Holleczek, Bernd; Schöttker, Ben; Brenner, Hermann (Journal of internal medicine, 2022)
Background Epidemiological studies consistently find low concentrations of 25-hydroxyvitamin D (25(OH)D) in blood to be associated with increased mortality, and a recent large-scale Mendelian randomization study strongly supports a causal relationship among individuals with low vitamin D status. Evolving evidence suggested that bioavailable or free 25(OH)D may better predict mortality. We aimed to compare the prognostic values of vitamin D-binding protein (VDBP), total, bioavailable, complementary “nonbioavailable”, and free 25(OH)D for total and cause-specific mortality in a large population-based cohort study of older adults from Germany. Methods Bioavailable, complementary “nonbioavailable”, and free 25(OH)D concentrations were calculated among 5899 participants aged 50-75 years, based on serum concentrations of total 25(OH)D, VDBP, and albumin. The cohort was followed with respect to total and cause-specific mortality from recruitment in 2001-2002 up to the end of 2018. Multivariable Cox proportional hazards regression models were used to assess the associations between various vitamin D biomarkers and mortality, and further stratified by vitamin D status. Results During a median follow-up of 17.1 years, 1739 participants died, of whom 575, 584, and 94 died of cardiovascular diseases, cancer, and respiratory diseases, respectively. Very similar inverse associations with total mortality (hazard ratio (HR) per standard deviation decrease: 1.17, 95% confidence interval (CI): 1.11, 1.24 for total 25(OH)D; HR: 1.14, 95% CI: 1.08, 1.21 for bioavailable 25(OH)D; HR: 1.12, 95% CI: 1.06, 1.18 for free 25(OH)D) and cause-specific mortalities were seen for all biomarkers of vitamin D status. The strongest associations were consistently seen for respiratory mortality. These inverse associations were strongest among participants with low vitamin D levels (<50 nmol/L). No significant associations were seen between VDBP and mortality. Conclusions Total, nonbioavailable, bioavailable, and free 25(OH)D showed very similar inverse associations with total and cause-specific mortality, which were strongest among those with low vitamin D status in this large population-based cohort.